Accelerated curing effects on the mechanical performance of cold bonded and sintered fly ash aggregate concrete. (15th February 2015) - Gomathi, P.; Sivakumar, A.
Graphical abstract: Highlights: Improving the stability of fresh cold bonded aggregate using alkali activator. Comparative assessment on the physical and mechanical properties of cold bonded aggregates. Maximum utilization fly ash aggregate concrete and its effect on the mechanical properties of concrete. Effect of accelerated curing techniques on the strength gain properties of fly ash aggregate incorporated concrete. Systematic evaluation of various durability properties of fly ash aggregate concrete mixes. Abstract: This study investigates the mechanical performance of concrete incorporating fly ash based light weight aggregates. Comparative assessment on the physical and mechanical properties of cold bonded and sintered fly ash aggregates were evaluated systematically. Design concrete mixes were theoretically arrived using aggregate packing concept with different combinations of two phase system (mortar and fly ash aggregate). Experimental test results indicated favorable mechanical strength improvements of concrete incorporating sintered fly ash aggregates compared to cold bonded aggregates. Test results also demonstrated that the composite strength of concrete was found to be improved when the ratio of volume of coarse aggregate to volume of cement mortar is lower. Most notably, the sintered fly ash aggregate (62%) substituted concrete mixes exhibited a maximum compressive strength of 39.97 MPa when subjected to hot water curing. In general, favorable strength gain properties were noted in the case of fly ash aggregate concrete specimens exposed to either accelerated steam or hot water curing. Effects on the strength properties of various fly ash aggregate concretes subjected to various durability tests were also reported in this study.